ANALISIS STRATEGI GURU DALAM MENERAPKAN KARAKTER DISIPLIN SISWA KELAS V DI SD NEGERI 05 LANDAU GARONG - Fatma, Rio; Asep Eka Nugraha; M. Akip (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
this study aims to describe the strategy of teachers in implementing the character of the discipline of fifth grade students in SD Negeri 05 Landau Garong, as well as identify the obstacles faced and the solutions undertaken by teachers. The background of the study is based on the phenomenon of low student discipline, such as late entering class, not collecting assignments on time, and lack of compliance with school rules. The study used qualitative methods with a descriptive approach. Subjects were teachers and students of Class V, while data collection techniques include observation, interviews, and documentation. The results showed that teachers implement strategies in the form of: (1) exemplary, (2) preparation of clear class Rules, (3) consistency in rule enforcement, (4) intensive communication with parents, and (5) integration of discipline values in learning tools. Obstacles faced include lack of attention from parents, the influence of the outside school environment, and low awareness of students. The teacher's solutions include strengthening communication with parents, providing motivation, enforcing logical consequences, and a personal approach to students. This study confirms that the teacher's strategy in shaping the character of discipline must be implemented consistently and supported by the cooperation of all parties. It is recommended that schools further strengthen character education programs and engage parents on an ongoing basis.